Finding Your Why: Developing Personal and Departmental Mission Statements - Christopher Jochum (Academic Chairpersons Conference Proceedings, 2020)
In this interactive workshop, presenters and participants will collaborate to learn how identify their leadership style in order to develop a personal mission statement. Participants will also learn how to replicate this process with their faculty to develop a departmental mission statement, thus contributing to departmental culture and cohesiveness.
Keywords: Leadership development; mission statements; leadership philosophy; departmental culture; departmental cohesiveness